Strategi Pengembangan Rumah Makan di Kawasan Pesisir Berbasis Geo-Tourism - Ratnah Ratnah; I Putu Suarta; Murdiani Sukarana; Hamsiati Hamsiati (LaGeografia, 2022)
AbstractThe potential for restaurants in coastal areas is very promising to be developed. This study aims to identify the development of restaurants in the coastal area, especially the Likupang coast in North Minahasa and the Galesong coast of Takalar Regency. This research is a type of quantitative research using survey methods. The population in this study are restaurant managers in coastal areas and consumers. The sampling technique used is the incidental technique of 256 respondents. The data collection techniques used were questionnaire, interview, observation, FGD, and literature study. And the data analysis technique used is an analysis with a Likert scale and SWOT analysis. The results of data analysis show that the existence of restaurants in coastal areas has enormous potential to be developed, this can be seen from the results of respondents' very positive perceptions of 4 indicators, namely services/HR, products, prices, and facilities/infrastructure. As for the analysis of internal factors, it can be seen that the strength (22) is greater than the weakness (19). And so is the analysis of external factors, opportunities (23) are greater than threats (18) so that the restaurant development strategy in coastal areas is formulated with 16 strategies consisting of W-O Strategy, W-T Strategy, S-O Strategy, and Strategy S – T each with 4 strategies.AbstrakPotensi Rumah Makan di kawasan pesisir sangat menjanjikan untuk dikembangkan. Penelitian ini bertujuan untuk mengidentifikasi pengembangan rumah makan di Kawasan pesisir khususnya pesisir Likupang di Minahasa Utara dan pesisir pantai Galesong Kabupaten Takalar. Penelitian ini termasuk jenis penelitian kuantitatif dengan menggunakan metode survey.  Populasi dalam penelitian ini adalah para pengelola rumah makan di kawasan pesisir dan konsumen. Teknik pengambilan sampel yang digunakan adalah teknik insdental sejumlah 256 responden. Adapun teknik pengumpulan data yang digunakan adalah questionnaire, wawancara, observasi, FGD, dan studi Pustaka. Dan Teknik analisis data yang digunakanan adalah analisis dengan skala Likert dan analisis SWOT. Hasil analisis data menunjukkan bahwa eksistensi rumah makan di Kawasan pesisir mempunyai potensi yang sangat besar untuk dikembangkan, hal ini terlihat dari hasil persepsi responden yang sangat positif terhadap 4 indikator, yaitu pelayanan/SDM, produk, harga, dan sarana/prasarana. Adapun pada analisis faktor internal terlihat bahwa kekuatan (22) lebih besar dari kelemahan (19). Dan begitu juga pada analisis faktor eksternal, peluang (23) lebih besar dari ancaman (18) sehingga  strategi pengembangan rumah makan di kawasan pesisir dirumuskan dengan 16 strategi yang terdiri atas Strategi W – O, Strategi W – T, Strategi S – O, dan Strategi S – T masing-masing dengan 4 strategi.